The problems of the illegitimate child (Walad Zina) and foundling (Laqit) in the sunni schools of law - Sujimon, Mohamad (IIUM Press, 2010)
This book addresses the views of the Sunni scholars regarding the importance of genealogical relationship (nasab) in Islamic family law and examines the role of legitimacy on the basis of the legal maxim “al-walad li al-firash”, evidence (al-bayyinah), and doubtful intercourse (wat’ shubhah). It also elucidates the views of the Sunni schools of law on how to establish illegitimacy. For the Sunni jurists, there are several situations that determine the illegitimacy of the child. A child is considered illegitimate if its birth is the outcome of adultery (zina) or the result of legitimate union but accompanied with imprecation (li‘an). Other circumstances include the birth of the child taking place in less than six lunar months, the father of the child being categorized as one who is incapable of begetting, or the birth as a result of marital relationship considered unlawful because of consanguinity. The book also deals comprehensively with the moral, religious, legal and other aspects of the illegitimate child and the foundling in the works of the Sunni jurists. The status and rights of the illegitimate child and the foundling in the Islamic family law of Malaysia and Brunei are also discussed by referring to some provisions from Federal Territory Act 1984 (Act 303) and Brunei law.